Chlorhexidine Bathing to Prevent Central Line–Associated Bloodstream Infections in Hematology Units: A Prospective, Controlled Cohort Study. (3rd September 2019) - Tien, Kuei-Lien; Sheng, Wang-Huei; Shieh, Shiouh-Chu; Hung, Yen-Ping; Tien, Hwei-Fang; Chen, Yi-Hsuan; Chien, Li-Jung; Wang, Jann-Tay; Fang, Chi-Tai; Chen, Yee-Chun
Abstract: Background: Chlorhexidine (CHG) bathing decreases the incidence of bloodstream infections in intensive care units, but its effect has been understudied in patients with hematological malignancies in noncritical care units. Methods: Adults with hematological malignancies hospitalized for cytotoxic chemotherapy in noncritical care units were offered daily 2% CHG bathing. We compared outcomes of patients who chose CHG bathing (CHG group) with outcomes of those who did not choose CHG bathing (usual-care group). The primary outcome was gram-positive cocci–related, skin flora–related, or central line–associated bloodstream infection. The negative control outcome was gut-origin bacteremia. Results: The CHG group (n = 485) had a crude incidence rate of the primary outcome that was 60% lower than the rate for the usual-care group (n = 408; 3.4 vs 8.4 per 1000 patient-days, P = .02) but had a similar crude incidence rate of the negative control outcome (4.5 vs 3.2 per 1000 patient-days; P = .10). In multivariable analyses, CHG bathing was associated with a 60% decrease in the primary outcome (adjusted hazard ratio [HR], 0.4; P < .001). In contrast, CHG bathing had no effect on the negative control outcome (adjusted HR, 1.1; P = .781). CHG bathing was well tolerated by participants in the CHG group. Conclusions: CHG bathing could be a highly effective approach for preventing gram-positive cocci–related, skin flora–related, or central line–associated bacteremia in patients with hematological malignancies who are hospitalized for cytotoxic chemotherapy in noncritical care units. Abstract : Patients with hematological malignancies hospitalized for myelosuppressive chemotherapy are at high risk of healthcare-associated infections, despite the use of oral antibacterial prophylaxis. Chlorhexidine bathing could be a simple, safe, and highly effective method for preventing central line–associated infection in such patients.